Teachers’ Perception toward the Quality of Writing Assessment - Honesty Yonanda Ayudhia; Didi Sukyadi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Writing assessment in senior high school is one of an interesting issue since assessing writing is not a simple task for the teachers. It requires some consideration for the teachers when comes to writing assessment, such as the limited time to let the students write, and even how to give a score to the students’ writing. Some researchers in their research about writing assessment argue about the issue such as validity and reliability of the writing assessment, yet it did not describe the other main points that build a good writing assessment. So, this paper will examine senior high school teachers’ perception toward the quality of writing assessment. The quality was based on five criteria; they are practicality, reliability, validity, authenticity, and washback factor. The population of this research was English teachers in Indonesia, and the respondents were taken by using random sampling technique. This descriptive research used open-ended questionnaire as an instrument. The result showed that the assessment that were usually used by teachers in writing class were reliable, valid and had washback effects. However, the assessment had not practical and authentic yet.